Revisiting Hofstede among South African students: some intercultural communication guidelines for the workplace - Schutte, Paul (Department of Communication Science, University of the Free State, 2009)
This research addressed two questions: (1) Are black and white students rather more different or similar concerning Hofstede’s cultural dimensions?; and (2) How should culture differences be accommodated during communication? A questionnaire was administrated among a sample of 1374 respondents, 50% black and 50% white students, from three different universities. The findings provided a glimpse of the “cultural software of the mind” of students who will be employees in different organisations in the near future. The findings indicate that there are more similarities than differences concerning the cultural dimensions, irrespective of biographical, racial or ethnic differences. The vast majority (83%) agreed that some form of accommodation should take place. Sixty three different suggestions have been mentioned by all respondents. It is noteworthy that the three with the highest frequency are the same for both groups: knowledge of the other culture, respect for them and the use of English as code for communication. This indicates and proves to a certain extent that, despite the existence of certain differences, these respondents are not only rather similar concerning the cultural dimensions alone, but also in their suggestions on how to accommodate cultural differences during their communication with people from another culture.
Keywords: Hofstede; South African students; Culture; Communication; Workplace; Black students; White students